An analysis of technical information for mechatronics research. (28th February 2020) - Osorio, Nestor L.; Osorio, Gabriel E.
Abstract : Purpose: Mechatronics is a very important area of research in industrial applications. The purpose of this study is to find some of the most important components of the literature on this subject. Design/methodology/approach: The analysis is based on the use of the database Compendex; it was searched in the broadest way for documents related to mechatronics. In addition, subject guides from libraries of universities with mechatronics programs were studied to find resources available in those areas. Findings: The literature of mechatronics is extensive and multidisciplinary. Based on the results from Compendex, the following data were found: most productive authors, list of leading journals and conference proceedings, publishers and grant organizations, authors' affiliations and other minor details. Based on the analysis of subject guides, the following types of resources were found: research databases, reference books and ebook collections. Research limitations/implications: Part of the analysis is based on a search performed in one technical database, Compendex; it was the database that generated the largest number of citations as compared to Inspec and the Web of Science. The results have a strong English language focus. It is possible that by using the results from multiple data bases, some additional sources could be obtained. Practical implications: Mechatronics is a relatively new technological field comprising a number of scientific and engineering areas. The results obtained summarized a significant amount of bibliographic information. Originality/value: The work is original; to the best of the authors' knowledge, no other study has analyzed the literature on this subject.